Antimicrobial Effect and Characterization of Exopolysaccharide Film from Aureobasidium pullulans YTP6-14 with Cinnamaldehyde - Srisookaiyaka, Jitmanee; Thaniyawan, Suthep; Thaniyavarn, Jiraporn; Morikawa, Masaaki; Borompichaichartkul, Chaleeda (Journal of Food Technology, Siam University, 2021)
This study describes antimicrobial properties of modified films prepared by incorporation of cinnamaldehyde (CH) into the solution of exopolysaccharide (EPS). EPS was produced by Aureobasidium pullulans YTP6-14 and partial physical properties were investigated. CH exhibited high antimicrobial activity against bacterial and fungal at low concentration. The highest and the lowest minimum inhibitory concentration (MIC) was observed against Staphylococcus aureus and Bacillus subtilis at 1.484 and 0.093 mg/mL, respectively. Film forming solutions containing CH 24 and 30 mg/mL were chosen to form the films. The film without CH was thin, smooth, homogeneous, colorless and odorless while the incorporated film was slightly thicker and inhomogeneous in the matrix, exhibited more yellow tinge, and less transparent with cinnamon odor. Moreover, the modified polysaccharide film with 30 mg/mL CH exhibited lower water vapor permeability. Amount of CH (%CH) was lost during film preparation (approximately 70%) and gradually decreased every week but remained higher than MIC value for at least 5 weeks. The antimicrobial activity of the films was observed in both culture broth and agar plate. The polysaccharide film with CH 30 mg/mL showed the highest antimicrobial activity against all strains.